NanoSSIEFARL polymeric nanoparticles-based immunotherapeutic for the treatment of genital herpes - Renata Zorzetto; Flávia Pires Peña; Aline Cláudio de Oliveira; Jayme de Castilhos Ferreira Neto; Gabriel Tardin Mota Hilario; Fernanda Teresa Bovi Frozza; Marvin Paulo Lins; Fernanda Poletto; Marcelo Jung Eberhardt; Pedro Roosevelt Torres Romão; Tanira Alessandra Silveira Aguirre; Luiz Carlos Rodrigues Junior (Polímeros)
Abstract This study aimed to investigate the therapeutic potential of a nanoparticle formulation containing the immunodominant peptide SSIEFARL from Herpes simplex virus 2 glycoprotein B A against genital herpes. A nanoparticle formulation (NanoSSIEFARL) was engineered and characterized for its physicochemical and immunomodulatory properties. NanoSSIEFARL displayed mean particle size of 212 ± 5 nm, polydispersity index of 0.12 ± 0.01 and zeta potential of -7.4 ± 2.5 mV, exhibiting spherical morphology. pH stability remained consistent over 30 days (day 0: 4.5 ± 0.5; day 30: 5.0 ± 0.5). A novel high-performance liquid chromatography method was validated for SSIEFARL quantification. Peptide association efficiency reached 98.3% ± 2.1, with 41.6% ± 4.4 peptide release from nanoparticles after 4 hours. Cytotoxicity assessment revealed cellular viability exceeding 90%, with macrophage uptake observed after 4 hours. Altogether, these results suggest that NanoSSIEFARL is a promising candidate for effective immunotherapy against genital herpes.